2006
DOI: 10.1529/biophysj.106.082388
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Generation by UVA Light Exposure of Endogenous Photosensitizers

Abstract: UVA light (320-400 nm) has been shown to produce deleterious biological effects in tissue due to the generation of singlet oxygen by substances like flavins or urocanic acid. Riboflavin, flavin mononucleotide (FMN), flavin adenine dinucleotide (FAD), beta-nicotinamide adenine dinucleotide (NAD), and beta-nicotinamide adenine dinucleotide phosphate (NADP), urocanic acid, or cholesterol in solution were excited at 355 nm. Singlet oxygen was directly detected by time-resolved measurement of its luminescence at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
222
1
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(239 citation statements)
references
References 39 publications
3
222
1
5
Order By: Relevance
“…However, in combination with UVA1 irradiation, riboflavin treatment could significantly impair cellular viability. It has been shown that UVA irradiation of riboflavin generates reactive intermediate species, such as singlet oxygen, superoxide anions, triplet state riboflavin radicals, and hydrogen peroxide (33)(34)(35). High-dose UVA irradiation alone has also been proven to produce reactive oxygen species with known cytotoxic properties (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, in combination with UVA1 irradiation, riboflavin treatment could significantly impair cellular viability. It has been shown that UVA irradiation of riboflavin generates reactive intermediate species, such as singlet oxygen, superoxide anions, triplet state riboflavin radicals, and hydrogen peroxide (33)(34)(35). High-dose UVA irradiation alone has also been proven to produce reactive oxygen species with known cytotoxic properties (36).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the decay time of the singlet oxygen luminescence signal increased up to 40 s at the highest protein concentration. Thus, it can be stated that (i) the generation of singlet oxygen requires sufficient oxygen concentration (19), and (ii) singlet oxygen can diffuse through different environments, such as bacteria and water.…”
Section: Singlet Oxygen Luminescence For Variable and High Bacterial mentioning
confidence: 99%
“…Recently, a model was developed to estimate the singlet oxygen dose by characterization of Photofrin (Axcan Pharma, Birmingham, AL) photobleaching during photodynamic therapy of eukaryotic cells in vitro (18). Moreover, singlet oxygen can be visualized by measuring its luminescence at 1,270 nm directly in solvents (19,20), in eukaryotic cells (21,22), and even in human skin (23). This time-resolved decay of the luminescence should provide an indication of the site of singlet oxygen in bacteria.…”
mentioning
confidence: 99%
“…Many lines of evidence have linked the oxidative damage generated by these species with the development of pathological conditions, such as atherosclerosis, neurodegenerative diseases, and cancer [1]. Singlet molecular oxygen [O 2 ( 1 ⌬ g )] is a reactive form of oxygen that can be produced by the action of peroxidases [2,3], UVA light in the presence of a sensitizer [4,5] and also during the dimerization reactions of peroxyl radicals in lipid peroxidation [6,7]. Electron-rich biomolecules, such as lipids, proteins, and DNA, can be important targets for O 2 ( 1 ⌬ g ) oxidation [8].…”
mentioning
confidence: 99%